The Bottom 20%: Early Career Paths of Adolescents with Low GPA - Jörgen Hansen; Nicolai Kristensen; Henrik Lindegaard Andersen (Institute of Labor Economics (IZA), 2020)
Across nations, large proportions of younger birth cohorts obtain no professional qualications. Using a structural dynamic approach, we analyze policies targeted adolescents who leave grade nine with a GPA in the bottom 20%. We find that preparatory courses, offered to young people who are unable to commence a qualifying degree, have no positive impact on future labor market outcomes. Unobservable noncognitive qualities are more important for this group than are cognitive skills. Education is a good option for some, but not for all. Implications for mechanism design and wage support schemes are discussed.
Keywords: I2; I38; 330; education; adolescents; structural dynamic programming